Callow in More Ways Than One: The Supreme Court Causes More Confusion in Contract - Maharaj, Krish (Ottawa Law Review / Revue de droit d’Ottawa, 2021)
This article addresses two significant misunderstandings, or perhaps a single larger misunderstanding, about the nature and scope of damages for breach of contract evident in the majority and concurring minority opinions in CM Callow Inc v Zollinger. The first misunderstanding is unique to the majority decision and pertains to the very idea of what expectation damages are, and confuses presumed “negative expectations” (i.e., things that ought not happen) with positive expectations of the kind ordinarily protected by contract and vindicated by contract/expectation damages. The second shared by the concurring minority and majority alike is a misunderstanding as to what the “least onerous method” standard for the assessment of expectation damages in contract means and how it applies in circumstances in which the defendant had a clearly available means of limiting its liability to the plaintiff. The article explains the errors made with respect to both issues and how they ought to have been thought of and understood to apply in the circumstances of the case and in contract more generally.